THE KINETICS OF THE PROCESS OF COUPLING THE WHEEL-RAIL - Savoskyn, O. M.; Liapushkin, M. M. (Science and Transport Progress, 2005)
The process of a wheel and a rail coupling is considered as the short-term physical interaction of surfaces of a wheel and a rail according to the basic concepts of solid body physics.